VALIDATION OF MEDIATION COMPETENCE IN SCHOOL ENVIRONMENT - Nicmane, Lolita Terēze; Baltušīte, Regīna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
We are living in uneasy and unusual times of sharp changes. The situation that arouse due to the spread of COVID-19 is causing serious stress for most of us, which implies emotional tension and hypersensitivity reaction to the information we hear or read. As a result, it leads to even more conflict situations than at any times. School is a part of society. The school environment is exposed to conflict situations both coming from outside and arising inside the school activity (internal conflicts). The ability to find a solution to a conflict implies the mediation competence of a school environment personnel and the students (other scientists call it conflict resolution competence). The aim of the research is to validate the necessity of mediation in school environment and to characterise the mediation competence. The methods of research used: 1) the analysis of theoretical insights and regulatory documents; 2) questionnaire survey; 3) reflection of personal experience. The theoretical research includes the assessment of the opinions of various authors in relation to the mediation competence and the necessity to promote it within the school environment. The empirical research analyses the data acquired by polling of school students (181), teachers (191) and parents (148). In total, 520 respondents participated in the survey. The article validates the necessity of mediation in school environment and the mediation competence. The assessment of the theoretical and empirical research testifies that the promotion of the mediation competence within a school environment is of high importance for all the parties involved in the educational process.